Enhanced production of recombinant proteins in Corynebacterium glutamicum using a molecular chaperone - Zhang, Fuming; Yang, Yankun; Liu, Chunli; Li, Ye; Bai, Zhonghu; Liu, Xiuxia; Linhardt, Robert J.; Wang, Yali (Journal of general and applied microbiology, 2023)
Protein synthesis in Corynebacterium glutamicum is critical for applications in biotechnology and medicine. However, the use of C. glutamicum for protein production is limited by its low expression and aggregation. To overcome these limitations, a molecular chaperone plasmid system was developed in this study to improve the efficiency of recombinant protein synthesis in C. glutamicum. The effect of molecular chaperones on target protein synthesis (Single-chain variable fragment, Scfv) under three different promoter strengths was tested. In addition, the plasmid containing the molecular chaperone and target protein was verified for growth stability and plasmid stability. This expression model was further validated using two recombinant proteins, human interferon-beta (Hifn) and hirudin variant III (Rhv3). Finally, the Rhv3 protein was purified, and analysis of Rhv3 activity confirmed that the use of a molecular chaperone led to an improvement in test protein synthesis. Thus, the use of molecular chaperones is believed to will improve recombinant proteins synthesis in C. glutamicum.